Health and quality of life vs. occupational activity - Małgorzata Kowalska; Szymon Szemik (Nofer Institute of Occupational Medicine, 2016)
The level of quality of life and health status of the population largely depends on the determinants related to occupational activity. The results of reviewed bibliography indicate a significant and growing importance of employment conditions on the quality of life and population health status in most countries of the world, especially in those with market economy. Of the evaluated determinants the following factors should be listed in particular: sources and the amount of income, stability of the income and employment, the nature of work and the degree of job satisfaction, as well as autonomy and career prospects. Moreover, they proved that the situation of persisting and long-term unemployment and precarious employment leads to a significant deterioration in the quality of life and health, especially among young people. In conclusion, the study of quality of life and population health status should take into consideration factors related to occupational activity. Med Pr 2016;67(5):663-671